SIMULATOR PEMBANGKIT LISTRIK TENAGA PIKO HIDRO UNTUK MODUL PRAKTIKUM DI LABORATORIUM KONVERSI ENERGI - Firdaus, Hendra; Suryadi , Dedi; Nurhayati , Maria (Universitas Majalengka, 2022)
Piko Hydro Power Plant Simulator is a tool that performs the process of imitating something real and its surroundings from a Piko Hydro Power Plant. The act of performing a simulation generally describes the key characteristics of the behavior of a physical system or system, the tool aims to introduce, explain and assist in the understanding of a tool on a larger scale. This study describes the results of measurements and testing of the Pico Hydro Power Plant (PLTPH) simulator and the manufacture of a practicum module. The simulator is designed to find out about the Hydro Power Plant (PLTA) scheme as a learning material. After the PLTPH simulator was tested, the water flow rate in the channel was 0.29 L/s and the head value was 22.85 meters, with a potential power of 450 W or 0.45 kW with a generator efficiency of 0.8 and a turbine efficiency of 0.9 and a total 4 pole generator pole and 1400 rpm speed. It is hoped that this research can make it easier for users to understand about hydroelectric power plants.